A new species of Brasilotyphlus (Gymnophiona: Siphonopidae) and a contribution to the knowledge of the relationship between Microcaecilia and Brasilotyphlus - Correia, Larissa Lima; Nunes, Pedro M. Sales; Gamble, Tony; Maciel, Adriano Oliveira; Marques-Souza, Sergio; Fouquet, Antoine; Rodrigues, Miguel Trefaut; Mott, Tamí (Zootaxa, 2018)
A third species of Brasilotyphlus, a siphonopid caecilian, is described based on six specimens from two twin mountains in Roraima state, northern Brazil. Brasilotyphlus dubium sp. nov. differs from all other congeners in having a combination of 123–129 primary annuli and 9–16 secondary annular grooves. The first molecular data were generated and analyzed for Brasilotyphlus, and the genus was recovered as monophyletic and nested within a paraphyletic Microcaecilia. The extent of genetic and taxonomic sampling, and moderate phylogenetic support are not considered sufficient enough to place Brasilotyphlus in the synonymy of Microcaecilia.